Evaluation of biocompatibility and osseointegration of Nb–xTi–Zr alloys for use as dental implant materials. (3rd March 2021) - Ou, Pinghua; Hao, Cong; Liu, Jue; Yang, Hailin; He, Rengui; Zhang, Taomei; Wang, Yali; Ruan, Jianming
Abstract: The aim of this study was to evaluate the biocompatibility and osteogenic potential of 50%Nb– x Ti–Zr (NTZ, x = 20%, 30%, 40% by weight) alloys as compared with dental commercial pure titanium (cpTi). Cell cytotoxicity assay, fluorescence microscopy and electron microscopy were used to measure the in vitro biocompatibility of NTZ. The expression of alkaline phosphatase (ALP), integrin β1, osteocalcin (OC), Ki67 and collagen-I (Col-I) at the mRNA level was measured by real-time reverse transcription-polymerase chain reaction. Osseointegration ability was determined using x-ray evaluation and histological analysis in vivo . Compared with the MG63 cells grown on cpTi on day 3, the viability, adherence and proliferation rates of cells cultured on NTZ alloys were significantly improved ( p < 0.05). Furthermore, similar expression levels of Ki67, Col-I, OC and ALP were found in the MG63 cells grown on NTZ alloys and those grown on cpTi. The Cbfα1 level was significantly higher for the 50%Nb–30%Ti–Zr (NTZ3) than for the cpTi group on day 6 ( p < 0.01), indicating that NTZ alloys can induce osteogenesis. A considerable amount of new bone formation and osseointegration was observed around NTZ3 implants compared with cpTi implants in vivo . Collectively, NTZ3 showed superior biocompatibility and osteogenic activity; therefore, NTZ3 may be an excellent replacement for dental Ti implants.